Come rain or shine: effects of external conditions on the properties of linyphiid silk - Wharton, Daniel; Weston, Nicola; Goodacre, Sara (Frontiers in Arachnid Science, 2025)
Spiders have adapted to a wide range of ecological niches, accompanied by the diversification of their silk, which performs various ecological functions under different environmental conditions. This study investigates the physical properties of silk produced by highly mobile linyphiid spiders, whose airborne silken “sails” enable long-distance, high-altitude windborne dispersal. Environmental Scanning Electron Microscopy imaging demonstrated that linyphiid silk interacts with moisture in its surroundings, leading to changes in stiffness and increased torsion at relative humidities greater than 60%. The estimated tensile strength under low moisture conditions is estimated to be up to 1 GPa but drops by the order of a factor of 2 when exposed to moisture (>60% relative humidity) or to short (30 minute) bursts of short wavelength (UV-C) light. In contrast, storage at temperatures ranging from -18°C to 70°C had no significant impact on tensile strength. These findings demonstrate the resilience of linyphiid silk to low temperatures typical of high altitudes, with important implications for understanding wind-assisted dispersal, global spider distribution, and potential responses to climate change. We also show that the silk can withstand exposure to ultraviolet light at intensities that would induce damage or death to living tissue, albeit with an increased likelihood of fracture. Together these findings provide important insights needed to understand ecological processes and explore uses and limitations of synthetic analogues of these biological materials in medicine and engineering.